Recent perspectives and crucial challenges on unitized regenerative fuel cell (URFC) - Ahmad Mohamad Pauzi,; Umi Azmah Hasran,; Sahriah Basri,; Nabila A. Karim, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Renewable sources of energy are becoming increasingly popular in recent years. The idea of using alternative energy that utilizes renewable sources is to slowly replace our dependence on fossil fuels. Conventional fossil fuels are not viable due to the fact that they are predominantly unsustainable over the long run. Furthermore, pollution will be reduced through the use of cleaner and more environmentally friendly renewable energy. Polymer electrolyte membrane fuel cell (PEMFC), which utilizes hydrogen as fuel, has a high potential as an alternative power generator. The unitized regenerative fuel cell (URFC) is a type of PEMFC that can perform both in charge mode (as a fuel cell) and discharge mode (as an electrolyzer). This review looks into the recent researches on the structure and different components of the URFC. In particular, emphasis is placed on bifunctional electrodes. Recent development in URFC research has produced a more stable bifunctional electrode with improved energy efficiency and overall stability and durability. Various works have been carried out to replace Pt as the electrocatalyst, including the use of graphene as a low cost non-metal graphene-based electrocatalyst. Electrocatalyst support also plays an important role in increasing conductivity while reducing the catalyst resistance to corrosion. The technological challenges and limitations of the URFC system are also discussed in this review.